Обґрунтування напрямів підвищення ефективності ринкової діяльності ТОВ "Навчально-відпочинковий комплекс "Зефір" на основі концепції соціально-відповідального маркетингу - Врублевський, Ілля Олександрович; Vrublevskyi, Illia Oleksandrovych (Національний університет "Львівська політехніка", 2024)
В роботі розглянуто основні аспекти та особливості концепції теорії соціальної відповідальності та соціально відповідального маркетингу зокрема, на підставі робіт зарубіжних та вітчизняних науковців, які обґрунтовують необхідність застосування принципів соціальної відповідальності у сфері бізнесу в сучасних умовах. Сучасний етап розвитку української економіки та суспільства характеризується тим, що залишаються незадоволеними морально-етичні потреби населення, що негативно позначається на психічному стані людей, а також слугує одним із тих факторів, які поглиблюють економічну кризу, утруднюють зростання прозорості ведення бізнесу в Україні. Тому з метою підвищення своєї конкурентоспроможності за рахунок поліпшення іміджу на ринку вітчизняні підприємства повинні активно впроваджувати заходи соціально відповідального бізнесу [1, c.24]. Соціальна відповідальність є важливою рисою сучасного бізнесу. Вона передбачає певний рівень добровільного відгуку на соціальні проблеми, виконання моральних вимог, які ставить суспільство. Компанії вже усвідомили переваги соціальної проактивної позиції й усе частіше й більш системно долучаються до вирішення соціальних і екологічних проблем. Соціальна політика повинна бути доповнена соціальною місією і стратегією діяльності в основних сферах сталого розвитку – соціальній та екологічній. Стратегічні компетенції компанії повинні бути спрямовані на досягнення рівномірних ефектів у соціальній та екологічній сферах і визначати перспективи розвитку суспільства загалом [3, c.18]. 4 Також розглянуті шляхи та методи, якими відбувається регулювання соціальної відповідальності бізнесу. Розкрито такі аспекти, як державне регулювання в сфері соціальної відповідальності бізнесу, яке є комплексним процесом, де поєднуються зовнішній контроль, внутрішня ініціатива та вплив суспільства, саморегуляція та корпоративні практики, ринкові механізми, громадянський тиск та громадські інститути, тощо. Зроблено висновок про комплексність процесу, коли поєднання зовнішнього контролю, внутрішньої ініціативи та впливу суспільства є найефективнішим методом регулювання соціальної відповідальності. В другій частині розглянуто сучасні світові тенденції розвитку та впровадження соціально-відповідальних ініціатив у маркетинговій діяльності, які характеризують поєднання екологічної, соціальної, фіскальної відповідальності та відповідальності перед персоналом. Розглянуто американську, європейську та японську моделі концепції соціальної відповідальності. Приділено увагу особливостям соціально відповідального маркетингу під час війни, таких як організація цільових фондів, допомога ЗСУ та ВПО, тощо. З повномасштабною військовою агресією 2022 року проти України значна частина бізнес-процесів була тимчасово трансформована чи змінена, що зумовило і модифікацію певних практичних напрямів реалізації КСВ [4, c.23]. В умовах воєнного стану в Україні підприємцям доводиться не тільки йти на економічні ризики, але й переживати самознищення та окупацію. Хоча війна в Україні триває достатньо довго, варто зазначити, що дослідники ще не до кінця проаналізували деталі впровадження механізмів корпоративної соціальної відповідальності (КСВ) в умовах бойових дій. [5, c.405]. Подано детальний аналіз організаційної структури, видів діяльності та діючої маркетингової стратегії ТОВ «НВК «Зефір». Оцінено рівень соціальної відповідальності керівництва та персоналу підприємства. 5 В третій частині роботи розроблено рекомендації у сфері соціально відповідального маркетингу для підвищення ефективності ринкової діяльності ТОВ «НВК «Зефір» та підвищення конкурентоздатності підприємства, серед аналогічних у галузі. Запропоновано заходи із забезпечення ефективності пропозицій та рекомендацій у концепцію соціально-відповідального маркетингу ТОВ «НВК «Зефір». Об’єктом дослідження є ТОВ «Навчально відпочинковий комплекс «Зефір». Предмет дослідження - теоретичні та прикладні засади впровадження концепції соціально-відповідального маркетингу в діяльності ТОВ «НВК Зефір». Мета дослідження – визначити та обґрунтувати основні напрямки підвищення ефективності ринкової діяльності ТОВ «НВК Зефір» на основі концепції соціально-відповідального маркетингу. Результати дослідження - розроблено рекомендації у сфері соціально-відповідального маркетингу та запропоновано заходи із забезпечення ефективності рекомендацій для вдосконалення стратегії соціально-відповідального маркетингу ТОВ "НВК "Зефір".

The article examines the theoretical aspects and features of the concept of social responsibility and socially responsible marketing, in particular, based on the works of foreign and domestic scholars who substantiate the need to apply the principles of social responsibility in business in modern conditions. The current stage of development of the Ukrainian economy and society is characterized by the fact that the moral and ethical needs of the population remain unsatisfied, which negatively affects the mental state of people, and also serves as one of the factors that deepen the economic crisis and hinder the growth of transparency of doing business in Ukraine. Therefore, in order to increase their competitiveness by improving their image in the market, domestic enterprises should actively implement socially responsible business measures [1, p.24]. Social responsibility is an important feature of modern business. It implies a certain level of voluntary response to social problems and fulfillment of moral requirements set by society. Companies have already realized the benefits of being socially proactive and are increasingly and systematically involved in addressing social and environmental issues. Social policy should be complemented by a social mission and strategy in the main areas of sustainable development - social and environmental. The strategic competencies of the company should be aimed at achieving uniform effects in the social and environmental spheres and determine the prospects for the development of society as a whole [3, p.18]. The ways and methods of regulating social responsibility of business are also considered. Such aspects as state regulation are disclosed, the sphere of social 8 responsibility of business is a complex process that combines external control, internal initiative and influence of society, self-regulation and corporate practices, market mechanisms, civil pressure and public institutions, etc. It is concluded that the process is complex, when a combination of external control, internal initiative and public influence is the most effective method of regulating social responsibility. The second part of the article examines the current global trends in the development and implementation of socially responsible initiatives in marketing activities, which are characterized by a combination of environmental, social, fiscal and personnel responsibility. The author analyzes the American, European and Japanese models of the social responsibility concept. Attention is paid to the peculiarities of socially responsible marketing during the war, such as the organization of trust funds, assistance to the AFU and IDP, etc. With the full-scale military aggression of 2022 against Ukraine, a significant part of business processes was temporarily transformed or changed, which led to the modification of certain practical areas of CSR implementation [4, p.23]. In the context of martial law in Ukraine, entrepreneurs not only have to take economic risks, but also experience self-destruction and occupation. Although the war in Ukraine has been going on for a long time, it is worth noting that researchers have not yet fully analyzed the details of the implementation of corporate social responsibility (CSR) mechanisms in the context of hostilities. [5, c.405] A detailed analysis of the organizational structure, types of activities and the current marketing strategy of «NVK «Zefir» LLC is given. The level of social responsibility of the company's management and staff is assessed. In the third part of the work, recommendations in the field of socially responsible marketing are developed to improve the efficiency of market activities of «NVK «Zefir» LLC and increase the competitiveness of the enterprise among similar ones in the industry. 9 Measures to ensure the effectiveness of the proposals and recommendations in the concept of socially responsible marketing of «NVK «Zefir» LLC are proposed. The object of the study is LLC "Educational and Recreational Complex "Zefir". Scope of research is the theoretical and applied principles of implementation of the concept of socially responsible marketing in the activities of «NVK «Zefir» LLC. Goal of research - to identify and substantiate the main directions of improving the efficiency of market activities of «NVK «Zefir» LLC on the basis of the concept of socially responsible marketing. The research findings - to develop recommendations in the field of socially responsible marketing and to propose measures to ensure the effectiveness of recommendations for improving the strategy of socially responsible marketing of «NVK «Zefir» LLC.
Justification of directions for increasing the market activities efficiency at "Educational and recreational complex "Zefir" Ltd based on the socially responsible marketing concept
Keywords: 3.075.00.00; – соціальна відповідальність; маркетинг; соціальна політика; ефективність; економічна діяльність; - social responsibility; marketing; social policy; efficiency; economic activity